2022-RA-1128-ESGO Has endometrial cancer treatment changed during the last years? A cancer registry data-based approach to monitor expected treatment changes after the release of the corresponding S3 guideline. (20th October 2022) - Schultz, Annemarie; Jobst, Niklas; Gebauer, Gerhard
Abstract : Introduction/Background: With approximately 11.000 new cases annually, endometrial cancer is the fourth most malignancy in women in Germany. In April 2018 the S3 endometrial cancer guideline was released as part of the Germany oncology guideline program to promote quality and transparency of medical care. The S3 guideline advised on various aspects of endometrial cancer treatment such as surgical strategies and adjuvant therapy. Recommendations of this S3 guideline have been implemented for more than four years. Very recently, the introduction of the molecular classification of endometrial carcinoma (EC) as a prognostic and predictive factor is going to challenge the morphological classification used so far. Based on cancer registry data we analysed how clinical practice has changed according to guideline recommendations. Methodology: A data set of patients with endometrial cancer diagnosed prior (2016–2017) and after (2019–2020) publication of the S3 guideline was extracted from the Hamburg Cancer Registry (HCR). Reports on diagnosis, treatment, and course of disease were evaluated and compared between both groups. Results: After publication of the S3 guideline changes in the treatment management of patients with endometrial cancer over time were observed in the Hamburg Cancer Registry data. Regarding surgical therapy, a decrease in lymphadenectomies performed in patients with low-risk type I endometrial cancer and changes in surgical techniques (such as open versus laparoscopic surgery) occurred. Conclusion: Our study demonstrates that cancer registry data can be used to monitor the reality of care for patients with endometrial cancer across institutions and sectors of treatment. In order to further improve this valuable source of data, more complete and comprehensive collection of cancer registry data should be intensively pursued.